Imaging of the Primary Visual Pathway based on Visual Deficits - Patel,Swapnil C.; Smith,Stephen M.; Kessler,Alexander T.; Bhatt,Alok A. (Journal of Clinical Imaging Science)
Vision loss can occur due to a variety of etiologies along the primary visual pathway. Understanding the anatomic organization of the visual pathway, which spans the globe to the occipital cortex, can help tailor neuroimaging to identify the cause of visual dysfunction. In this review, relevant anatomy and optimization of computed tomography and magnetic resonance imaging techniques will be described. This will be followed by a discussion of imaging findings related to pathologies at each functional anatomic level.